Respuesta :
[tex]2x^2 +6x+1=-4x^2 + 1 \\ \\ 6x^2 + 6x=0 \\ \\ x^2 + x=0 \\ \\ x(x+1)=0 \\ \\ x=0, -1 \\ \\ \\ x=0 \implies y=1 \\ \\ x=-1 \implies y=-3[/tex]
So, the solutions are (x,y)={(0,1), (-1,-3)}
Answer:
(0, 1) and (-1, -3)
Step-by-step explanation:
Given quadratic equations:
[tex]\begin{cases}y=2x^2+6x+1\\y=-4x^2+1\end{cases}[/tex]
Solve by the method of substitution by substituting the first equation into the second equation:
[tex]\implies 2x^2+6x+1=-4x^2+1[/tex]
Add 4x² to both sides:
[tex]\implies 2x^2+6x+1+4x^2=-4x^2+1+4x^2[/tex]
[tex]\implies 6x^2+6x+1=1[/tex]
Subtract 1 from both sides:
[tex]\implies 6x^2+6x+1-1=1-1[/tex]
[tex]\implies 6x^2+6x=0[/tex]
Factor out the common term 6x:
[tex]\implies 6x(x+1)=0[/tex]
Apply the zero-product property:
[tex]\implies 6x=0 \implies x=0[/tex]
[tex]\implies (x+1)=0 \implies x=-1[/tex]
Substitute the found values of x into one of the equations and solve for y:
[tex]\textsf{When } \: x = 0\implies y=-4(0)^2+1=1[/tex]
[tex]\textsf{When } \: x = -1\implies y=-4(-1)^2+1=-3[/tex]
Therefore, the solutions to the given system of equations are (0, 1) and (-1, -3).
Learn more about systems of equations here:
https://brainly.com/question/27930827
https://brainly.com/question/28164947